Antibiotic resistance spectrums of Escherichia coli and Enterococcus spp. strains against commonly used antimicrobials from commercial meat-rabbit farms in Chengdu City, Southwest China - Sun, Chen; Wang, Ziye; Li, Yan; Huang, Jian (Frontiers in Veterinary Science, 2024)
Antimicrobial resistance (AMR) is commonly associated with the inappropriate use of antibiotics during meat-rabbit production, posing unpredictable risks to rabbit welfare and public health. However, there is limited research on the epidemiological dynamics of antibiotic resistance among bacteria indicators derived from local healthy meat-rabbits. To bridge the knowledge gap between antibiotic use and AMR distribution, a total of 75 Escherichia coli (E. coli) and 210 Enterococcus spp. strains were successfully recovered from fecal samples of healthy meat-rabbits. The results revealed that diverse AMR phenotypes against seven commonly used antimicrobials, including ampicillin (AMP), amoxicillin-clavulanic acid (A/C), doxycycline (DOX), enrofloxacin (ENR), florfenicol (FFC), gentamicin (GEN), and polymycin B (PMB), were observed among most strains of E. coli and Enterococcus spp. in two rabbit farms, although the distribution pattern of antibiotic resistance between young and adult rabbits was similar. Among them, 66 E. coli strains showed resistance against 6 antimicrobials except for PMB. However, 164 Enterococcus spp. strains only exhibited acquired resistance against DOX and GEN. Notably, the DOX-based AMR phenotypes for E. coli and Enterococcus spp. strains were predominant, indicating the existing environmental stress conferred by DOX exposure. The MICs tests suggested elevated level of antibiotic resistance for resistant bacteria. Unexpectedly, all GEN-resistant Enterococcus spp. strains resistant high-level gentamicin (HLGR). By comparison, the blaTEM, tetA, qnrS and floR were highly detected among 35 multi-resistant E. coli strains, and aac[6']-Ie-aph[2']-Ia genes widely spread among the 40 double-resistant Enterococcus spp. strains. Nevertheless, the presence of ARGs were not concordant with the resistant phenotypes for a portion of resistant bacteria. In conclusion, the distribution of AMR and ARGs are prevalent in healthy meat-rabbits, and the therapeutic antimicrobials use in farming practice may promote the antibiotic resistance transmission among indicator bacteria. Therefore, periodic surveillance of antibiotic resistance in geographic locations and supervisory measures for rational antibiotic use are imperative strategies for combating the rising threats posed by antibiotic resistance, as well as maintaining rabbit welfare and public health.